Peat modification integrating Geopolymer and fly ash. (May 2019) - Mohamed Jais, I B; Abdullah, N; Md Ali, M A; Johar, M A
Abstract: Peat is known of its high compressibility, low shear strength, natural moisture content and long-term settlement. This indicates that peat is problematic, and it is necessary to improve the soil so that it can be used for supporting foundations. Fly ash is one of the source materials for geopolymer binders and available abundantly worldwide. It is considered as eco-friendly when it is used in the construction industry since it is a recycled material. A geopolymer mix known as Geopolymer Flexible Activator (GeoFlexA) and fly ash is used as an alternative solution to solve ground settlement issues related to soft soils. The purpose of this research is to modify peat by binding GeoFlexA and fly ash together. This research is carried out to determine the effect of GeoFlexA admixture and fly ash to the strength of peat. The index property tests include moisture content, organic content, fibre content, specific gravity and pH test only. Compaction test and Unconfined Compressive Test (UCT) is used to prepare samples and to analyse the strength respectively. The UCT was conducted after the samples were prepared in the mould and allowed to cure under 0, 7, 14, 28 and 56 days. Various percentages of fly ash used are 5%, 10%, 15% and 20% while a constant GeoFlexA admixture is used at 40% of the soil weight. The experimental results demonstrated that the compressive strength of the modified peat increases significantly with the fly ash content and curing time. These indicated that the mixture of GeoFlexA and fly ash can promote to an enhanced compressive strength of peat, hence, become a potential admixture for modifying peat.